A system-level assessment of solar power contribution to EV - Kong, Cherlynn. (2012)
An approach to determine the extent by which electric vehicle (EV) batteries in a typical battery swapping station can be charged through the photo-voltaic (PV) system is described. Using solar irradiation data from Singapore, a statistical approach is used to predict the amount of solar energy that can be captured at a battery swapping station. The energy level or state of charge (SOC) of the EV batteries is modelled using various statistical distribution models to analyse the energy needed to fully charge one EV battery at a specified confidence level. With solar and vehicular statistics, it is possible to estimate the extent of solar PV contribution and assess the grid power demand of a battery swapping station.